Determination of alpha-beta arteether in pharmaceutical products using direct injection micellar liquid chromatography - Dubey S.; Bose D.; Shukla S.K.; Durgbanshi A.; Esteve-Romero J.; Carda-Broch S. (My University, 2025)
A simple and easy liquid chromatographic procedure was developed for the separation and analysis of β-arteether. The developed method uses a reversed-phase Luna C18 column (250 mm × 4.6 mm), a hybrid micellar mobile phase containing 0.15 M SDS-6% (v/v) butanol-0.01 M phosphate buffered at pH 7, and detection at 218 nm. Under these conditions, the analysis time was less than 6 min. Validation studies were performed according to the International Conference on Harmonization guideline, including linearity (R2 > 0.9998) in the 0.1-50 g/mL range, accuracy (99.8-100.8%), repeatability [RSD (%) 1.8-2.8], intermediate precision [RSD (%) 1.8-2.9], and robustness, which were found satisfactory. Method was applied to the determination of β-arteether in different pharmaceutical preparations and wrapper/label free ampoules obtaining recoveries in the 97.7-102.2% range. Compared to other chromatographic techniques, micellar liquid chromatography has the advantages of avoiding sample extraction from matrices, thus reducing the global analysis time and environmental toxicity. © 2014 Taylor and Francis Group, LLC.